VD_FINDINFO Décision / 2009 / 131 vom 6. Oktober 2009 - VD Tribunal cantonal (2009)
RADIATION DU RÔLE | 13 LAI, 38 LPGA, 53 al. 3 LPGA, 60 al. 1 LPGA, 61 let. a LPGA, 55 LPA-VD, 83 LPA-VD, 94 al. 1 let. c LPA-VD, 95 LPA-VD